Expression of human Cfdp1 gene in Drosophila reveals new insights into the function of the evolutionarily conserved BCNT protein family. - Messina, G.; Atterrato, M.T.; Fanti, L.; Giordano, E.; Dimitri, P. (Scientific reports, 2016)
The Bucentaur (BCNT) protein family is widely distributed in eukaryotes and is characterized by a highly conserved C-terminal domain. This family was identified two decades ago in ruminants, but its role(s) remained largely unknown. Investigating cellular functions and mechanism of action of BCNT proteins is challenging, because they have been implicated in human craniofacial development. Recently, we found that YETI, the D. melanogaster BCNT, is a chromatin factor that participates to H2A.V deposition. Here we report the effects of in vivo expression of CFDP1, the human BCNT protein, in Drosophila melanogaster. We show that CFDP1, similarly to YETI, binds to chromatin and its expression results in a wide range of abnormalities highly reminiscent of those observed in Yeti null mutants. This indicates that CFDP1 expressed in flies behaves in a dominant negative fashion disrupting the YETI function. Moreover, GST pull-down provides evidence indicating that 1) both YETI and CFDP1 undergo homodimerization and 2) YETI and CFDP1 physically interact each other by forming inactive heterodimers that would trigger the observed dominant-negative effect. Overall, our findings highlight unanticipated evidences suggesting that homodimerization mediated by the BCNT domain is integral to the chromatin functions of BCNT proteins.